PENGARUH MODIFIKASI MEDIA BUDIDAYA JAMUR TIRAM (Pleurotus ostreatus Jacq. ex Fr. Kummer) TERHADAP MORFOLOGI, PERTUMBUHAN, DAN KANDUNGAN PROTEIN - , MELLIA BUDIARTI, Rina Sri Kasiamdari, S.Si, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
White oyster mushrooms (Pleurotus ostreatus Jacq. ex Fr. Kummer) is one of edible mushrooms. Oyster mushroom ha s high proteins than other mushroom. Besides that, the morphology of oyster mushroom has important economic values on the market. The morphology and growth of oyster mushroom are influenced by cultivation media used. The aims of this research were to study morphology, the growth and the protein content of oyster mushrooms on modification of cultivation media. There were four media used in this research there were : sawdust, baggase,weeds leaves and sorghum. The result showed that P.ostreatus on sawdust, baggase, weeds leaves and sorghum media had different morphology, such as : white fruiting bodies